PEMBATASAN PERIODESASI ANGGOTA LEMBAGA LEGISLATIF DALAM PERSPEKTIF NEGARA HUKUM MODERN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia is a rule of law, in the understanding of a rule of law, there are characteristics of restrictions on power, Law Number 17 of 2014 concerning MD3 and in Law Number 8 of 2012 concerning General Election of Legislative Members, there is no regulation regarding the limitation of the term of office of members of the DPR and DPD which is also automatic for MPR membership. The limitation on the periodicity of members of the legislative body is very necessary given the many problems that occur within the power of the legislative body, including high levels of corruption coupled with a low level of trust and satisfaction from the community, making this institution need new people who are innovative, have integrity and understand. meaning of representation. The urgency of limiting the periodization of members of the legislative body in Indonesia to create democratic politics, to improve people's welfare, and to ensure that one's power is not absolute.This type of research is normative legal research, namely using literature study to search the data. This research is descriptive in nature which tries to provide data as thorough and as detailed as the existing problems. In writing this study using qualitative data analysis which means explaining and concluding about the urgency of limiting the periodicity of members of the legislative body and the ideal concept of limiting the periodicity of members of the legislature in Indonesia that have been collected by the author. This research uses secondary data or codified scientific data.The results of this study explain that there is no regulation regarding the limitation of periodicity of members of the legislative body in Indonesia, the limitation of periodization aims to create democratic politics, namely to ensure that leadership rotation runs well, limitation of the periodicity of members of the legislative body aims to improve the welfare of the people by always providing wide opportunities. to become a member of the legislature, as well as limiting the periodicity of members of the legislative body aims to guarantee a person's power so that it is not absolute according to the principles of a modern rule of law. the ideal concept of limiting the term of office of members of the legislative body in Indonesia. First, the restrictions are carried out in the same way as the President's term, namely for two terms. Second, the restriction is carried out in the same way as the term of office of the Senate of the Philippines, namely for two terms with each term for six years. Third, the limitation is carried out for three periods with each period of 5 years.Keywords: Restrictions- Periodization- Legislative